Devenir « une belle jeune fille » : construction du genre dans les cours d’éducation sexuelle dispensés à des filles en situation de handicap - Sophie Torrent (Genre, Sexualité et Société)
Specialized sex education is aimed for students with disabilities. In French-speaking Swiss schools, it is provided by sexual health specialists. How does the process of « doing gender » (West & Zimmermann, 2009) happens in these courses? The content of the discourses of the professionals during the classes taught to girls with an intellectual disability was analyzed through filmed lessons. Three trends are revealed by this analysis: (1) the assignment to a sex category when the student does not perceive their sexual identity, (2) the obligation to be happy about their feminine condition and (3) the control of gender when femininity is deemed as exacerbated and hence as dangerous to the student. Thus, sexual health specialists not only support the construction of femininity, but also participate in the making of a « good » femininity. These trends illustrate the complexity of the work of professionals and the difficulty for specialized sex education to extricate itself from gender norms.